Blending Proteins in High Moisture Extrusion to Design Meat Analogues: Rheological Properties, Morphology Development and Product Properties - Wittek, Patrick (Foods, 2021)
High moisture extrusion (HME) of meat analogues is often performed with raw materials containing multiple components, e.g., blends of different protein-rich raw materials. For instance, blends of soy protein isolate (SPI) and another component, such as wheat gluten, are used particularly frequently. The positive effect of blending on product texture is well known but not yet well understood. Therefore, this work targets investigating the influence of blending in HME at a mechanistic level. For this, SPI and a model protein, whey protein concentrate (WPC), were blended at three different ratios (100:0, 85:15, 70:30) and extruded at typical HME conditions (55% water content, 115/125/133 °C material temperature). Process conditions, rheological properties, morphology development, product structure and product texture were analysed. With increasing WPC percentage, the anisotropic structures became more pronounced and the anisotropy index (AI) higher. The achieved AI from the extrudates with a ratio of 70:30 (SPI:WPC) were considerably higher than comparable extrudates reported in other studies. In all extrudates, a multiphase system was visible whose morphology had changed due to the WPC addition. The WPC led to the formation of a much smaller dispersed phase compared to the overlying multiphase structure, the size of which depends on the thermomechanical stresses. These findings demonstrate that targeted mixing of protein-rich raw materials could be a promising method to tailor the texture of extruded meat analogues.